Evaluation of a program to prevent political violence in the Basque conflict: effects on the capacity of empathy, anger management and the definition of peace Evaluación de un programa para la prevención de la violencia política en el conflicto vasco: efectos en la capacidad de empatía, el control de la ira y la definición de paz - Maite Garaigordobil (Elsevier, 2012)
Objective: To assess the effects of a program for the prevention of political violence on empathy, expression of feelings of anger, and the capacity to define peace-violence. Method: This study used a quasi-experimental design with pretest-posttest repeated measures and a control group. The sample comprised 276 adolescents aged between 15 and 17 years (191 in the experimental group, 85 in the control group; 127 boys and 149 girls). A battery of three assessment instruments was administered before and after the intervention. The aim of the program was to increase sensitivity to the victims of political violence, promote respect for human rights, and prevent violence. The intervention consisted of 10 sessions over 3 months. Results: MANOVA analyses revealed that the program increased participants' capacity of empathy (perspective-taking), anger control in annoying situations, and capacity to define peace-violence. Conclusions: This study has practical educational implications and provides an intervention tool that enhances the development of personality during adolescence and may have a preventive effect on violent behavior. Objetivo: Evaluar los efectos de un programa para prevenir la violencia política en la capacidad de empatía, la expresión de sentimientos de ira y la definición de paz-violencia. Método: El estudio utilizó un diseño cuasiexperimental de medidas repetidas pretest-intervención-postest con grupo de control. La muestra está configurada con 276 adolescentes de 15 a 17 años de edad; de ellos, 191 son experimentales y 85 controles, 127 hombres y 149 mujeres. Se administró una batería de tres instrumentos de evaluación antes y después de aplicar el programa de intervención. El objetivo del programa fue incrementar la sensibilidad hacia las víctimas de la violencia política, promover el respeto por los derechos humanos y prevenir la violencia. La intervención consistió en 10 sesiones realizadas durante 3 meses. Resultados: Los resultados del MANOVA revelaron que el programa incrementó la capacidad de empatía (toma de perspectiva), el control de la ira en situaciones de enfado y la capacidad para definir paz-violencia. Conclusiones: Este estudio tiene implicaciones prácticas y provee una herramienta de intervención para fomentar el desarrollo de la personalidad durante la adolescencia. Por ello, puede tener un efecto preventivo de la conducta violenta.